Mekanisme Pembentukan Burr pada Pemesinan Frais Mikro Ti 6Al- 4V ELI dalam Keadaan Kering - Saputra, Endra; Ibrahim, Gusri Akhyar; Harun, Suryadiwansa; Supriyadi, Eko Agus; Patihawa, Armulani (Jurnal Rekayasa Mesin, 2020)
One of the ingredients that are popular now is titanium, but titanium is a material that is difficult to process using conventional milling machining because of the poor thermal conductivity of the material so that the high-temperature machining process produced in the cutting zone causes plastic deformation in cutting tools and increased chemical reactivity in titanium. High-speed micro-milling machining can be used for micromachining of hard metals or alloys that are difficult to achieve at low speeds. Micro milling machining in titanium material 6Al-4V ELI with variations in milling knife diameter 1 and 2 mm, spindle speed 10.000 and 15.000 rpm, feed 0,001 and 0,005 mm / rev, depth of cut 100 and 150 Î¼m, which then do data processing using the method Taguchi full factorial and theoretical analysis. The results showed that the diameter of the tool and into the cut had the greatest effect on burr formation, the greater the diameter of the milling blade resulted in the formation of shorter and smaller burrs, the use of a 1 mm diameter milling blade and a 150 Î¼m depth cut gave rise to long burr formations and tight, while the use of a 2 mm diameter milling blade and a cutting depth of 100 Î¼m give rise to a short and slight burr formation.